Synergistically improving electrocatalytic performance and CO2 tolerance of Fe-based cathode catalysts for solid oxide fuel cells. (1st August 2022) - Gao, Juntao; Ma, Dan; Zhao, Hui; Li, Qiang; Lü, Zhe; Wei, Bo
Abstract: Fe-based pervoskite oxides Bi0.5 Sr0.5 Fe1− x Zr x O3− δ (BSFZ x, x  = 0, 0.05, 0.10 and 0.15) were synthesized and developed by doping of cation Zr as possible cathodes for solid oxide fuel cells (SOFCs). Herein, we carefully investigated the effect of Zr-doped on BSFZ x physicochemical property. The Bi0.5 Sr0.5 Fe0.90 Zr0.10 O3− δ (BSFZ0.10) cathode shows the lowest R p values ranging from 0.52 to 0.11 Ω cm 2 in the temperature range of 600–700 °C and the corresponding activation energy is about 1.135 eV. A single fuel cell with BSFZ0.10 cathode delivers a satisfactory electrocatalytic performance with a peak power density (PPD) as high as 1.2 W cm −2 at 700 °C. The BSFZ0.10 also exhibits unsurpassed stability by less change in R p values under different CO2 concentrations (5, 10 and 15 vol%). The excellent chemical stability and CO2 tolerance of BSFZ x electrode material is mainly due to the doping of highly acidic Zr 4+ and the increase of average metal bond energy (ABE). The present work highlights that BSFZ x oxides are very promising candidate cathode catalysts for oxygen-conducting SOFCs. Graphical abstract: Image 1 Highlights: BSFZ x cathodes are studied for applications in SOFCs. Peak power density of single cell with BSFZ0.10 cathode reaches 1.2 W cm −2  at 700 °C. Oxygen reduction kinetics of BSFZ0.10 cathode is studied. BSFZ0.10 cathode shows excellent CO2 tolerance.